Analisis Integritas Pegawai Puskesmas Tambakaji dalam Manajemen Penetapan Istithaah Kesehatan Jemaah Haji Lansia - Fasihullisan, Azka Faqih; Affandi, Yuyun; Rozaq, Abdul (Kamaya: Jurnal Ilmu Agama, 2025)
Elderly pilgrims who have high risk are a special concern for the government. This study aims to determine the implementation of employee integrity, the managerial system for determining istithaah, and factors that affect decision-making. The research method used is qualitative with a descriptive approach, data collection through interviews. The subject of the study involves health center employees in 2024. The results of the study show that the implementation of employee integrity refers to the standards from the Ministry of Health and the decree of the Minister of Health (KMK), in the istithaah management system starting from socialization planning then the first stage of examination then the stage of entering data into Siskohatkes, the factor that affects the decision-making of the feasibility of istithaah is the suitability of medical data. In 2018 there were pilgrims who routinely died, and were sent to the holy land, causing concern for the hajj officers and the pilgrims concerned to be sent home first not according to the group. In 2024, employees of the Tambakaji Health Center will be declared to have sufficient integrity.